2022
DOI: 10.1002/nbm.4882
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of colorectal cancer organoids: A comparison between high‐resolution magic angle spinning magnetic resonance spectroscopy and solution nuclear magnetic resonance spectroscopy of polar extracts

Abstract: Patient‐derived cancer cells cultured in vitro are a cornerstone of cancer metabolism research. More recently, the introduction of organoids has provided the research community with a more versatile model system. Physiological structure and organization of the cell source tissue are maintained in organoids, representing a closer link to in vivo tumor models. High‐resolution magic angle spinning magnetic resonance spectroscopy (HR MAS MRS) is a commonly applied analytical approach for metabolic profiling of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In the future, we hope to extend our approach to enable similar quantitative metabolic flux measures in hESC-derived COs using indirect 13 C-or 2 Hlabelled glucose administration, as demonstrated previously in in vivo magnetic resonance spectroscopy (MRS) studies [14][15][16][17] . Lastly, van der Kemp et al 18 reported a comparison between HR-MAS NMR spectroscopy of intact colorectal cancer organoids, and solution NMR spectroscopy of polar extracts. While the van der Kemp et al study finds that metabolic measures are highly correlated between intact cancer organoids and tissue extracts, the study also highlights the benefits of studying intact tissue, since it is non-destructive and enables the potential to conduct follow-up analyses such as omics analyses or histology.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we hope to extend our approach to enable similar quantitative metabolic flux measures in hESC-derived COs using indirect 13 C-or 2 Hlabelled glucose administration, as demonstrated previously in in vivo magnetic resonance spectroscopy (MRS) studies [14][15][16][17] . Lastly, van der Kemp et al 18 reported a comparison between HR-MAS NMR spectroscopy of intact colorectal cancer organoids, and solution NMR spectroscopy of polar extracts. While the van der Kemp et al study finds that metabolic measures are highly correlated between intact cancer organoids and tissue extracts, the study also highlights the benefits of studying intact tissue, since it is non-destructive and enables the potential to conduct follow-up analyses such as omics analyses or histology.…”
Section: Discussionmentioning
confidence: 99%